Direct Isomaltulose Synthesis From Beet Molasses by Immobilized Sucrose Isomerase - Wang, Qin-Qing; Yang, Ming; Hao, Jian-Hua; Ma, Zai-Chao (Frontiers in Bioengineering and Biotechnology, 2021)
Isomaltulose is becoming a focus as functional sweetener for sucrose substitute. However, isomaltulose production using sucrose as the substrate caused high cost. In this work, beet molasses (BM) was introduced as the substrate to produce isomaltulose for the first time. Firstly, immobilized sucrose isomerase (SIase) was proved mostly efficient for isomaltulose synthesis from pretreated BM. Then, the conditions of immobilized SIase-catalyzing reaction were optimized. The optimal conditions were 800 g/L pretreated BM, pH 5.5 and 15 U/g SIase dosage, respectively. Immobilized SIase used in repeated batch reaction showed good reusability for converting BM into isomaltulose. The conversion rate of sucrose in pretreated BM remained high level (97.5%) within the first 8 batch (even above 94% after 11 batches), achieving 446.4 ± 5.5 g/L isomaltulose with 85.8% purity. Importantly, significant cost reduction of feedstock costs was also confirmed by economic analysis. These results indicated this green and feasible process would be an effective, economic, and reliable for industrial isomaltulose production.